The Enforcement of Pollution Control Laws: Inspections, Violations, and Self-Reporting - Helland, Eric (The Review of Economics and Statistics, 1998)
Targeting is the practice of inspecting firms most likely to violate a regulation. This paper provides empirical evidence on the role of targeting in regulatory compliance. I propose that self-reporting by a firm is used to demonstrate that firms are willing to cooperate. The results indicate that there is a one-quarter penalty period following a violation. Inspections are also determined by the economic situation of the surrounding community, demonstrating that targeting opens the door to interestgroup influence. Inspections that detect violations encourage selfreporting, showing that firms demonstrate their desire to cooperate with regulators by disclosing violations.